KERAGAAN USAHA PENGGEMUKAN SAPI POTONG DI KABUPATEN CIAMIS - Isyanto, Agus Yuniawan; Sudrajat, Sudrajat (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2019)
The beef cattle fattening farming in Ciamis Distrcit has the potential to increase regional economy and farmer income. The study was carried out using literature studies using secondary data which was analyzed descriptively to describe the performance of beef cattle fattening farming in Ciamis District. The results showed that beef cattle fattening farming in Ciamis District needed to be developed through increased production, productivity and efficiency supported by government policies.